Warm Mesoclimate Advances the Seasonal Dynamics of Harmonia axyridis in Urban Habitats - Honek, Alois; Skuhrovec, Jiří; Martinkova, Zdenka; Kulfan, Ján; Jauschova, Terézia; Zach, Peter (Frontiers in Ecology and Evolution, 2021)
In 2016–2019, seasonal changes in the abundance of the harlequin ladybird Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) were established in the city center of Prague, Central Europe, and in its outskirts. Adults were sampled from lime trees (Tilia spp.) at regular intervals throughout the growing season. The abundance of H. axyridis paralleled the course of abundance of its prey, the aphid Eucallipterus tiliae L., which peaks either early or late in the season. As a result, the seasonal dynamics of H. axyridis were unimodal, with a peak in the early (late June – early July of 2017 and 2019) or late (late July – mid-September of 2016 and 2018) period of the season. In the early period, there was a small (1–4 days) difference in the timing of the peak of H. axyridis between the city center and the outskirts. In the late period, the peak occurred significantly earlier (by 13–21 days) in the city center due to the warmer climate there than in the outskirts. The difference in the timing of the population peak between both locations disappeared after recalculating the calendar to thermal time (number of day degrees above 10.6 °C thresholds elapsed from the end of H. axyridis hibernation). The warm mesoclimate of the city center advances the seasonal dynamics of H. axyridis, contributing to the success of this invasive species in urban habitats.